Edible mushrooms from Malaysia; a literature review on their nutritional and medicinal properties - Samsudin, Nik Iskandar Putra; Abdullah, N. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Mushrooms have been consumed by mankind for millennia. In Malaysia, there are many species of edible mushrooms which are either cultivated (Agaricus spp., Auricularia spp., Pleurotus spp.) or harvested in the wild (Ganoderma spp., Polyporus spp., Termitomyces spp.). With the advancement of technology, numerous discoveries have been made that elucidated the nutritional (high in fibres, proteins, vitamins; low in fats, cholesterols, sodium) and medicinal (anti-oxidative, anti-hypertensive, neuritogenesis) properties of edible mushrooms, all of which are highly beneficial for the maintenance of human health and well-being. This review thus compiles and documents the available literatures on edible mushrooms reported from Malaysia complete with scientific, English, and vernacular names for future references; provides a comprehensive and updated overview on the nutritional and medicinal properties edible mushrooms reported from Malaysia; and identifies the research gaps to promote further research and development on edible mushrooms reported from Malaysia. Overall, Malaysia is and remains a natural repository for wild and cultivated edible mushrooms. Deeper investigation on their nutritional and medicinal properties will certainly serve as an impetus for economic as well as scientific progress.